Creative industries and knowledge replication - Łukasik, Paweł (Przemysły kreatywne i replikacja wiedzy, 2019)
The concept of creative industries is becoming popular in recent years. Therefore, many publications deal with this topic. Nevertheless, fewer of them are dedicated to managerial issues. Most publications concentrate on the scope of creative industries and their influence on economy and society. The first aim of this paper is to present the specificity of management of organization in creative industry and its activity. The second aim is to collect and cite different definitions of knowledge replication to explain the meaning of the notion of knowledge replication. The third aim is to show the role of knowledge replication for organization’s activity in creative industries. The article also contains an introduction concerning different approaches to definition and classification of creative industries
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 3, s. 10-15
Keywords: creative industries; management; knowledge replication; przemysły kreatywne; replikacja wiedzy